TNF superfamily control of tissue remodeling and fibrosis - Steele, Hope; Cheng, Jason; Willicut, Ashley; Dell, Garrison; Breckenridge, Joey; Culberson, Erica; Ghastine, Andrew; Tardif, Virginie; Herro, Rana (Frontiers in Immunology, 2023)
Fibrosis is the result of extracellular matrix protein deposition and remains a leading cause of death in USA. Despite major advances in recent years, there remains an unmet need to develop therapeutic options that can effectively degrade or reverse fibrosis. The tumor necrosis super family (TNFSF) members, previously studied for their roles in inflammation and cell death, now represent attractive therapeutic targets for fibrotic diseases. In this review, we will summarize select TNFSF and their involvement in fibrosis of the lungs, the heart, the skin, the gastrointestinal tract, the kidney, and the liver. We will emphasize their direct activity on epithelial cells, fibroblasts, and smooth muscle cells. We will further report on major clinical trials targeting these ligands. Whether in isolation or in combination with other anti-TNFSF member or treatment, targeting this superfamily remains key to improve efficacy and selectivity of currently available therapies for fibrosis.